Factor influencing job involvement in Universiti Malaysia Perlis (UniMAP) - Sukri, Suriani; Asogan, Priyadharesheni; Waemustafa, Waeibrorheem (MCSER Publishing, Rome-Italy, 2015)
This paper attempts to identify the relevant factors that create a massive collision on the job involvement at Universiti Malaysia Perlis (UniMAP). The sample of 110 was drawn from academic staff which are divided into categories of professor, associate professor, senior lecturer and lecturer. The results indicated that job involvement of UniMAP academic staffs is depends on the three dimension factor of job involvement in workplaces which are motivation, organizational citizenship behavior and job satisfaction. Among three factors tested in this study, UniMAP academic staff agreed that organizational citizenship behavior and job satisfaction influenced their job involvement. However, it is found that motivation has no significant relationship with job involvement of UniMAP academic staff.